TrkB dependent adult hippocampal progenitor differentiation mediates sustained ketamine antidepressant response. Issue 1 (December 2017) - Ma, Zhenzhong; Zang, Tong; Birnbaum, Shari; Wang, Zilai; Johnson, Jane; Zhang, Chun-Li; Parada, Luis
Abstract Adult neurogenesis persists in the rodent dentate gyrus and is stimulated by chronic treatment with conventional antidepressants through BDNF/TrkB signaling. Ketamine in low doses produces both rapid and sustained antidepressant effects in patients. Previous studies have shed light on post-transcriptional synaptic NMDAR mediated mechanisms underlying the acute effect, but how ketamine acts at the cellular level to sustain this anti-depressive function for prolonged periods remains unclear. Here we report that ketamine accelerates differentiation of doublecortin-positive adult hippocampal neural progenitors into functionally mature neurons. This process requires TrkB-dependent ERK pathway activation. Genetic ablation of TrkB in neural stem/progenitor cells, or pharmacologic disruption of ERK signaling, or inhibition of adult neurogenesis, each blocks the ketamine-induced behavioral responses. Conversely, enhanced ERK activity viaNf1 gene deletion extends the response and rescues both neurogenic and behavioral deficits in mice lacking TrkB. Thus, TrkB-dependent neuronal differentiation is involved in the sustained antidepressant effects of ketamine. The precise mechanism for the sustained antidepressant action of ketamine is unclear. This study shows ketamine can promote neuronal differentiation via TrkB-ERK activation in mice and the sustained behavioral effect is attenuated when adult neurogenesis is blocked, but extended when it is enhanced.